Analisis Kualitas Pelayanan Publik di Kantor Kecamatan Kota Masohi Kabupaten Maluku Tengah - Bastian, Izak; Rahawarin, Mohamad Arsad; Selanno, Hendry (Jurnal Ilmiah Administrasita', 2025)
This study aims to analyze the quality of public services at the Masohi City Sub-District Office, Central Maluku Regency, from the perspective of service users. Using a qualitative descriptive approach, the research explores the experiences, perceptions, and expectations of the community regarding public service delivery. Data were collected through in-depth interviews, participatory observation, and document analysis to obtain a comprehensive understanding of the service process and its influencing factors. The study focuses on five dimensions of service quality: tangible, reliability, responsiveness, assurance, and empathy. The findings indicate that the tangible dimension, including physical facilities and infrastructure, provides a basic foundation for service quality, though some improvements are needed to enhance user comfort. Reliability reflects the ability of staff to deliver consistent and accurate services, while responsiveness and empathy demonstrate the staff’s readiness and attentiveness to community needs. The assurance dimension shows that the competence, professionalism, and trustworthiness of staff foster confidence among service users. Despite several strengths, there are areas for improvement, particularly in optimizing physical facilities, administrative procedures, and communication to ensure faster, more efficient, and more satisfactory services. This study concludes that public service quality at the Masohi City Sub-District Office is generally satisfactory but requires continuous improvement. Enhancing staff performance, facilities, and user interaction can increase community satisfaction and strengthen the professional image of the Sub-District Office as a reliable and responsive public service provider.